2014
DOI: 10.3390/cancers6031691
|View full text |Cite
|
Sign up to set email alerts
|

Oral Human Papillomavirus (HPV) Infection among Unvaccinated High-Risk Young Adults

Abstract: Oral HPV infection, the cause of most oropharyngeal cancer in the U.S., is not well studied among high-risk young adults. Men (n = 340) and women (n = 270) aged 18–25 years attending Baltimore County STD clinics were recruited if they declined HPV vaccination. Each participant had a 30-second oral rinse and gargle sample tested for 37 types of HPV DNA, and a risk-factor survey. Factors associated with prevalent infection were explored using log binomial regression. Men had higher prevalence of any oral HPV (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
1
20
2
Order By: Relevance
“…This can be attributed to the fact that the patients they studied may have had some type of sexually transmitted disease. Regarding smoking and alcohol consumption, it can be clearly seen that alcohol is more prevalent than smoking, finding that coincides with those of D'Souza et al 7 The effects of smoking and alcohol on HPV in the oral mucosa remains unclear. On the one hand, stimulation of the harmful elements would cause a thickening of the oral mucosa and eventually increased keratinization of it 14 , preventing a potential HPV infection in the basal layer of the oral epithelium.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This can be attributed to the fact that the patients they studied may have had some type of sexually transmitted disease. Regarding smoking and alcohol consumption, it can be clearly seen that alcohol is more prevalent than smoking, finding that coincides with those of D'Souza et al 7 The effects of smoking and alcohol on HPV in the oral mucosa remains unclear. On the one hand, stimulation of the harmful elements would cause a thickening of the oral mucosa and eventually increased keratinization of it 14 , preventing a potential HPV infection in the basal layer of the oral epithelium.…”
Section: Discussionsupporting
confidence: 74%
“…Sanchez et al 18 and D'Souza et al 7 reported similarly high rates regarding sexual habits. However, unlike our study, they found a high prevalence of HPV in the oral mucosa in both sexes.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A population-based study in the USA reported a higher prevalence of oral HPV infection in men compared with women (10.1% (95% CI 8.3 to 12.3) vs. 3.6% (95% CI 2.6 to 5.0), respectively, p<0.001) 46. Another study showed that men had a higher prevalence of oral HPV infection and suggested that cunnilingus may confer a higher risk of acquiring oral HPV infection than fellatio 17. Studies have shown an increased incidence of HPV-related HNSCC in men as compared with women, but the reasons are unclear 10 17 19 20 35 43 45.…”
Section: Differences In Sexual Behaviours By Age and Gendermentioning
confidence: 98%
“…In fact, there is little awareness among health professional regarding HPV infection and its role in HNSCC. Patients also lack information concerning the risks associated with HPV infection 17. The aim of this review of the literature is to determine whether there is strong evidence to correlate oral sex with HNSCC, thus suggesting patients should be counselled regarding sexual behaviour.…”
Section: Introductionmentioning
confidence: 99%